Germline mismatch repair gene variants analyzed by universal sequencing in Japanese cancer patients. (6th August 2019) - Kiyozumi, Yoshimi; Matsubayashi, Hiroyuki; Horiuchi, Yasue; Higashigawa, Satomi; Oishi, Takuma; Abe, Masato; Ohnami, Sumiko; Urakami, Kenichi; Nagashima, Takeshi; Kusuhara, Masatoshi; Miyake, Hidehiko; Yamaguchi, Ken
Abstract: Background: Lynch syndrome (LS) is the commonest inherited cancer syndrome caused by pathogenic variants of germline DNA mismatch repair (g. MMR ) genes. Genome‐wide sequencing is now increasingly applied for tumor characterization, but not for g .MMR . The aim of this study was to evaluate the incidence and pathogenicity of g. MMR variants in Japanese cancer patients. Methods: Four g. MMR genes ( MLH1, MSH2, MSH6, and PMS2 ) were analyzed by next generation sequencing in 1058 cancer patients (614 male, 444 female; mean age 65.6 years) without past diagnosis of LS. The g. MMR variant pathogenicity was classified based on the ClinVar 2015 database. Tumor MMR immunohistochemistry, microsatellite instability (MSI), and BRAF sequencing were also investigated in specific cases. Results: Overall, 46 g. MMR variants were detected in 167 (15.8%) patients, 17 likely benign variants in 119 patients, 24 variants of uncertain significance (VUSs) in 68 patients, two likely pathogenic variants in two patients, and three pathogenic variants in three (0.3%) patients. The three pathogenic variants included two colorectal cancers with MLH1 loss and high MSI and one endometrial cancer with MSH6 loss and microsatellite stability. Two likely pathogenic variants were shifted to VUSs by ClinVar (2018). One colon cancer with a likely benign variant demonstrated MLH1 loss and BRAF mutation, but other nonpathogenic variants showed sustained MMR and microsatellite stability. Conclusions: Universal sequencing of g. MMR genes demonstrated sundry benign variants, but only a small proportion of cancer patients had pathogenic variants. Pathogenicity evaluation using the ClinVar database agreed with MSI, MMR immunohistochemistry, and BRAF sequencing. Abstract : This is the first Japanese paper analyzing more than 1000 cancer patients on germline mismatch repair (MMR) genes and associated molecular assays followed by counseling. Pathogenicity evaluation of MMR genes judged by ClinVar 2018 but not by that of 2015 was compatible with the MMR immunohistochemistry, microsatellite instability status, and BRAF mutation.